End of life care pathways in the Emergency Department and their effects on patient and health service outcomes: An integrative review. (March 2022) - Heufel, Melissa; Kourouche, Sarah; Angela Lo, Wing-Shan; Thomas, Benjamin; Hood, Lucy; Curtis, Kate
Highlights: End of life screening and care pathways are feasible in the emergency department. Care pathways are thought to improve quality and consistency of end of life care. Further research to investigate patient and health service outcomes is required. Abstract: Introduction: End of life (EOL) care in the Emergency Department (ED) requires focused, person-centred care to meet the needs of this vulnerable cohort of patients. Methods: An integrative review of the literature using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline was conducted. Studies were included if they were primary research relating to patients in the ED at the EOL, and/or evaluated EOL care pathways in the ED. Databases OVID Emcare, OVID Medline, and Scopus were searched from 1966-September 2021; followed by screening and appraisal. Articles were compared and data grouped into categories. Results: Eleven research articles were included generating three categories for EOL care in ED. 1) tools/criteria to identify patients who may require EOL care in ED; 2) processes for providing EOL care, and 3) implementation methods/frameworks to support the uptake of EOL care processes. Conclusion: There were some commonalities in the criteria used to identify patients who may be at their EOL and the interventions implemented thereafter. There was no standardised process for screening for or treating EOL care needs in the ED. Further research is required to determine the impact that EOL care pathways have on patient and health service outcomes to inform strategies for future policy development.